Appearance
question:A set of 50 numbers has an arithmetic mean of 38. If the numbers 45 and 55 are removed from this set, what is the arithmetic mean of the remaining numbers? (A) 38.5 (B) 37.5 (C) 37 (D) 36.5 (E) 36
answer:1. **Calculate the initial sum of the 50 numbers:** We know from the problem that the average of the 50 numbers is 38. The sum of these 50 numbers can be calculated as follows: [ text{Sum} = text{Average} times text{Number of elements} = 38 times 50 = 1900 ] 2. **Determine the sum after removing two numbers (45 and 55):** Removing the numbers 45 and 55 from the set affects the sum: [ text{New Sum} = text{Initial Sum} - 45 - 55 = 1900 - 45 - 55 = 1800 ] 3. **Calculate the new number of elements:** Since we removed two numbers from the original 50 numbers, we have: [ text{New Number of elements} = 50 - 2 = 48 ] 4. **Calculate the new average:** The new average is given by the new sum divided by the new number of elements: [ text{New Average} = frac{text{New Sum}}{text{New Number of elements}} = frac{1800}{48} ] Performing the division: [ frac{1800}{48} = 37.5 ] # Conclusion: The arithmetic mean of the remaining 48 numbers is: [ boxed{B} ]
question:Determine the value of (x + y) where ((x,y)) is the center of the circle with the equation (x^2 + y^2 = 4x 6y + 9).
answer:First, rearrange the given circle equation by moving all terms to one side: [ x^2 - 4x + y^2 + 6y = 9 ] Next, complete the square for both the (x) and (y) terms: - For (x): Add and subtract (left(frac{-4}{2}right)^2 = 4), so: [ x^2 - 4x + 4 = (x-2)^2 ] - For (y): Add and subtract (left(frac{6}{2}right)^2 = 9), so: [ y^2 + 6y + 9 = (y+3)^2 ] Now, add these constants to the right side of the equation: [ (x-2)^2 + (y+3)^2 = 9 + 4 + 9 = 22 ] The equation of the circle in standard form is now: [ (x-2)^2 + (y+3)^2 = 22 ] Thus, the center of the circle is ((2, -3)). Therefore, [ x + y = 2 + (-3) = boxed{-1} ]
question:Given proposition p: (x+1)(2x) geq 0; proposition q: The inequality x^2 + 2mx m + 6 > 0 always holds for x. (1) If proposition q is true, find the range of real numbers m. (2) If p is a sufficient but not necessary condition for q, find the range of real numbers m.
answer:(1) From (x+1)(2-x) geq 0, we get: -1 leq x leq 2, thus, when p is true: x in [-1, 2]; If the inequality x^2 + 2mx - m + 6 > 0 always holds, then Delta = 4m^2 - 4(-m+6) < 0, solving this gives: -3 < m < 2, so, when q is true, m in (-3, 2); (2) If p is a sufficient but not necessary condition for q, i.e., p subsetneq q, from p: [-1, 2] subsetneq (-3, 2], thus, m in (-3, 2]. Therefore, the solutions are: (1) For q to be true, m in boxed{(-3, 2)}; (2) For p to be a sufficient but not necessary condition for q, m in boxed{(-3, 2]}.
question:Given a positive integer k and an integer aequiv 3 pmod{8} , show that a^m+a+2 is divisible by 2^k for some positive integer m .
answer:1. **Express (a) in terms of (x):** Given (a equiv 3 pmod{8}), we can write (a) as: [ a = 8x + 3 ] for some integer (x). 2. **Lemma: (v_2(a^{2^{k-2}} - 1) = k):** We need to show that the 2-adic valuation of (a^{2^{k-2}} - 1) is (k). 3. **Proof using the Lifting The Exponent (LTE) lemma:** By the LTE lemma, for (a = 8x + 3) and (n = 2^{k-2}), we have: [ v_2(a^{2^{k-2}} - 1) = v_2(a - 1) + v_2(2^{k-2}) ] Since (a = 8x + 3), we have: [ a - 1 = 8x + 2 ] Therefore: [ v_2(a - 1) = v_2(8x + 2) = v_2(2(4x + 1)) = 1 + v_2(4x + 1) ] Since (4x + 1) is odd, (v_2(4x + 1) = 0). Thus: [ v_2(a - 1) = 1 ] Also: [ v_2(2^{k-2}) = k-2 ] Therefore: [ v_2(a^{2^{k-2}} - 1) = 1 + (k-2) = k-1 ] This contradicts the lemma, so we need to re-evaluate the LTE application. Instead, we use: [ v_2(a^2 - 1) = v_2((8x + 3)^2 - 1) = v_2(64x^2 + 48x + 8) = 3 + v_2(8x^2 + 6x + 1) ] Since (8x^2 + 6x + 1) is odd, (v_2(8x^2 + 6x + 1) = 0). Thus: [ v_2(a^2 - 1) = 3 ] Therefore: [ v_2(a^{2^{k-2}} - 1) = v_2(a^2 - 1) + v_2(2^{k-3}) = 3 + (k-3) = k ] 4. **Induction for (k = 1, 2, 3):** For (k = 1, 2, 3), we can take (m = 1). 5. **Assume (2^k mid a^m + a + 2) and (2^{k+1} nmid a^m + a + 2):** Suppose: [ a^m + a + 2 equiv 2^k pmod{2^{k+1}} ] 6. **Consider (a^{2^{k-2}} - 1 equiv 2^k pmod{2^{k+1}}):** We have: [ a^{2^{k-2}} - 1 equiv 2^k pmod{2^{k+1}} ] 7. **Evaluate (a^{m + 2^{k-2}} + a + 2):** [ a^{m + 2^{k-2}} + a + 2 = (a^m + a + 2) + a^m(a^{2^{k-2}} - 1) ] Since: [ a^{2^{k-2}} - 1 equiv 2^k pmod{2^{k+1}} ] We get: [ a^m(a^{2^{k-2}} - 1) equiv a^m cdot 2^k pmod{2^{k+1}} ] Therefore: [ a^{m + 2^{k-2}} + a + 2 equiv (2^k + 2^k) pmod{2^{k+1}} equiv 0 pmod{2^{k+1}} ] Hence: [ 2^{k+1} mid a^{m + 2^{k-2}} + a + 2 ] (blacksquare)